A GENERALIZED SKEWED EXPONENTIAL DISTRIBUTION WITH APPLICATION TO UNEMPLOYMENT AGE DISTRIBUTION - Khoo, Wooi Chen; Ong, Seng Huat (Malaysian Journal of Science, 2019)
This paper introduces a generalization of the weighted or skewed exponential distribution. The motivation to consider this generalization stems from the interest in modelling unemployment data. The generalized skewed exponential distribution is shown to be log-concave, and as a consequence, a number of properties of the distribution are obtained. The generalized skewed exponential distribution is shown to give much better fit than the skewed exponential, Weibull, lognormal and logistic distributions for the unemployment age data.